1986
DOI: 10.1159/000183666
|View full text |Cite
|
Sign up to set email alerts
|

Effects of a Low Phosphorus, Low Nitrogen Diet Supplemented with Essential Amino Acids and Ketoanalogues on Serum Triglycerides of Chronic Uremic Patients

Abstract: The effects were studied of a vegetarian low-protein, low-phosphorus diet supplemented with essential amino acids and ketoanalogues and those of maintenance hemodialysis (MHD) and free diet on the serum triglycerides (STG) of 85 patients with chronic renal failure. Following dietary therapy STG decreased significantly in the 61 male patients (from 185.7 ± 89.8 to 153.5 ± 68.7 mg/dl; p < 0.001), whereas in the females the decrease was not significant (from 189.1 ± 83.9 to 167.0 ± 62.2 mg/dl; NS). When patients … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
7
0

Year Published

1987
1987
2007
2007

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(8 citation statements)
references
References 7 publications
1
7
0
Order By: Relevance
“…As to the male patients, our results are quite similar to those reported by Ciardella et al [1]. In the female group, the mean value of STG was in the normal range before the supplemented diet, but the few females patients with high STG levels did not show any improvement on the supple mented diet, whereas all the male patients lowered their STG after the supplemented diet.…”
supporting
confidence: 91%
See 1 more Smart Citation
“…As to the male patients, our results are quite similar to those reported by Ciardella et al [1]. In the female group, the mean value of STG was in the normal range before the supplemented diet, but the few females patients with high STG levels did not show any improvement on the supple mented diet, whereas all the male patients lowered their STG after the supplemented diet.…”
supporting
confidence: 91%
“…The recent and interesting article of Ciardella et al [1] prompted us to investigate the value of serum triglycer ides (STG) in our patient group before and 3 months after a low-protein (0.3 g/kg/day) low-phosphorus (6-8 mg/ kg/day) diet supplemented with essential amino acids and ketoanalogues.…”
mentioning
confidence: 99%
“…[34,35] In addition, a vegetarian low-protein regimen has been reported to reduce in a parallel way proteinuria and serum total and LDL cholesterol in nephrotic patients. [36] Moreover, a cross-sectional study including nonnephrotic patients with severe renal failure showed that a vegetarian low-protein diet was associated with a better 532 A. Cupisti et al…”
Section: Dyslipidemiamentioning
confidence: 99%
“…They are par tially corrected by LPDs [92] but the possi ble influence of AA or KA diets on such dis orders has not been fully evaluated and needs further study. However, suppression of parathyroid hormone excess by FLA ther apy has been reported to correct hypogona dism in male subjects and thus result in improvement of hypertriglyceridemia [93].…”
Section: Questions To Be Solved For Improved Utilization Of Aa and Kamentioning
confidence: 99%